Designing financial systems in East Asia and Japan - Fan, Joseph P.H.; Hanazaki, Masaharu; Teranishi, Juro (London: RoutledgeCurzon, 2004)
This book is an outgrowth of the conference n ''designing financial systems in East Asia and Japan: towards a 21st century paradigm''. It deliberates on some urgent issues that face the new architecture of the financial systems in Japan and East Asia.
Includes bibliographical references and index.
rua 12/10/16, ijb 07/02/2019
Loans
Keywords: Corporate governance; Economic history; Financial institutions; Financial crisis; Japan; East Asia